Meningkatkan kualitas air konsumsi rumah tangga dikecamatan Sabangparu Kab Wajo - Taufiq Natsir; Ahmad Rifqi Asrib (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The problem experienced by the people in the Sabbangparu sub-district today is that the well water that is in the home environment does not fulfill the requirements as drinking water, which is very murky physically containing soil elements with high iron and manganese content. In addition, river water taken directly through the pipe connection is also turbid and not yet through the purification filter. The community takes river and lake water for household consumption only to be collected and deposited which will be used for various household needs such as drinking, bathing, washing and other purposes. The limited supply of clean water that meets health requirements, both physically, biologically and chemically shows that there is a need for appropriate technology to treat water adapted to environmental conditions. For this reason, through science and technology activities for the community, it is expected that there will be an increase in public knowledge about water treatment techniques that are not feasible to be used, namely by making a clean water treatment system. The approach method that will be used is counseling, workshops and coaching / mentoring. Thus the output of science and technology for this community is (1) technique or. Safe, easy and inexpensive water treatment methods. (2) Household-scale water treatment equipment with a capacity of 500 liters, (3) Septic tank models and environmentally-friendly infiltration, (4) Published articles.